2015
DOI: 10.2217/fvl.15.64
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Management of the HIV/HCV Coinfected Patient

Abstract: Chronic hepatitis C virus (HCV) is a global epidemic, affecting approximately 150 million individuals throughout the world. The implications of HCV infection have been magnified in those who are infected with both HCV and the HIV as liver disease progression, liver failure and liver-related death are increased, particularly in those without well-controlled HIV disease. The development of direct-acting antiviral agents for HCV that allow shorter treatment periods with increased efficacy and decreased adverse ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…77 New direct-acting antiviral treatments are costly, but have low toxicity, short treatment durations, and can cure hepatitis C virus in more than 90% of patients, irrespective of HIV status. 78 An internationally funded hepatitis C elimination strategy in Georgia has allowed prisoners to access this treatment, but it is not accessible elsewhere in EECA prisons due to cost constraints. 79 …”
Section: The Confluence Of Mass Incarceration Substance Use Disordermentioning
confidence: 99%
“…77 New direct-acting antiviral treatments are costly, but have low toxicity, short treatment durations, and can cure hepatitis C virus in more than 90% of patients, irrespective of HIV status. 78 An internationally funded hepatitis C elimination strategy in Georgia has allowed prisoners to access this treatment, but it is not accessible elsewhere in EECA prisons due to cost constraints. 79 …”
Section: The Confluence Of Mass Incarceration Substance Use Disordermentioning
confidence: 99%
“…However, recent findings have suggested that HCV may not be a sole contributor to the increased prevalence of COPD [21]. So, the effect of HCV infection could be magnified in HIV/HCV coinfected patients [22]. …”
Section: Introductionmentioning
confidence: 99%
“…Currently, with the advancement in HCV therapies and increased rate of HIV/HCV coinfection being simultaneously treated, new drug–drug interactions have become a concern . The effects may manifest in changes in systemic or tissue exposure of the DAA or ARV.…”
Section: Drug Interactions In Haart Era and Todaymentioning
confidence: 99%
“…The interaction pathways of some current DAAs can be rather complex, with agents being substrates, inhibitors, or inducers of multiple metabolic and transporter pathways . In addition, DAAs with different mechanisms of action are given in combination to increase efficacy and decrease the chance of resistant virus emerging.…”
Section: Clinical Pharmacology Of New Hcv Daasmentioning
confidence: 99%
See 1 more Smart Citation